Demand for implementation of social media tools in primary health Centre for health promotion communication: A special reference to Ernakulum district - Shaji, Sujitha; Babu, S.Dinesh (International Journal of Psychosocial Rehabilitation, 2020)
Primary Health Centres are state owned health providers in India, played as the first level of health services to the community. Rural people mostly depend upon Primary Health Centre (PHC) for obtaining the information related to health promotion, especially at the time of epidemic diseases. Kerala Primary Health Centres are poorly equipped to provide this service because of inadequate communication tools. This study mainly focused on the existing communication methods and demand for implementation of social media tools for health promotion initiatives of PHC. Ernakulam district was chosen as the study area with 525 samples. Data are randomly collected with self-structured questionnaire. Tables and figures are used to analyse the collected raw data. Result showed that majority of the beneficiaries are unaware about the PHC services and free care facilities provided because of lack of proper communication facilities.